2010
DOI: 10.1111/j.1365-2222.2010.03536.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Entopy’: local allergy paradigm

Abstract: Allergy is defined as an immediate hypersensitivity type I immunological disease, which can be IgE or non-IgE driven, and in the latter case may be antibody or cell mediated. Atopy is a term used to describe individuals with a genetic predisposition for developing IgE-mediated allergic disease. But more recently, it has become evident that IgE-mediated disease can occur in non-atopic subjects. While it is now generally accepted that mucosal local IgE has a role in the expression of atopic allergic disease, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 81 publications
(101 reference statements)
2
29
0
3
Order By: Relevance
“…Some children with nonallergic rhinitis who had symptoms of rhinoconjunctivitis or nasal symptoms upon exposure to inhaled allergens could have local allergic rhinitis, without circulating, specific, IgEs. [25][26][27] We did not examine the noses of children in our study, and therefore cannot exclude this possibility. However, among these children, only 1 of 36 had allergic rhinitis at age 8 years.…”
Section: Discussionmentioning
confidence: 76%
“…Some children with nonallergic rhinitis who had symptoms of rhinoconjunctivitis or nasal symptoms upon exposure to inhaled allergens could have local allergic rhinitis, without circulating, specific, IgEs. [25][26][27] We did not examine the noses of children in our study, and therefore cannot exclude this possibility. However, among these children, only 1 of 36 had allergic rhinitis at age 8 years.…”
Section: Discussionmentioning
confidence: 76%
“…Patients who manifest symptoms similar to AR during the allergen season but do not show elevated serum IgE levels are classified as non-allergic rhinitis (NAR) [2], [5], [6]. However, studies have shown that within NAR patients, some are indeed “allergic” and have locally increased IgE levels in their nose or nasal lavage [7][9]. This type of rhinitis with local IgE production is defined as local allergic rhinitis (LAR) [7] or entopy [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown that within NAR patients, some are indeed “allergic” and have locally increased IgE levels in their nose or nasal lavage [7][9]. This type of rhinitis with local IgE production is defined as local allergic rhinitis (LAR) [7] or entopy [8], [9]. LAR is characterized by the local production of IgE in the nose, a Th2 pattern of mucosal cell infiltration, and positive nasal provocation test (NAPT), although serum antigen-specific IgE is negative [7].…”
Section: Introductionmentioning
confidence: 99%
“…Specific IgE identified using the enzyme allergosorbent test (EAST) can be detected in nasal secretions but not in the serum of these patients [1]. This type of allergy is limited to the nasal mucosa and therefore referred to as local allergic rhinitis [2,3], entopy [4] or allergic rhinitis with a negative skin test [5]. Clinical symptoms, nasal secretions and the profile of cytokine production of local allergic rhinitis are similar to classic allergic rhinitis [6,7].…”
Section: Introductionmentioning
confidence: 99%